2022
DOI: 10.1371/journal.pone.0271289
|View full text |Cite
|
Sign up to set email alerts
|

The Internal–External Locus of Control Short Scale–4 (IE-4): A comprehensive validation of the English-language adaptation

Abstract: The Internal–External Locus of Control Short Scale–4 (IE-4) measures two dimensions of the personality trait locus of control with two items each. IE-4 was originally developed and validated in German and later translated into English. In the present study, we assessed the psychometric properties (i.e., objectivity, reliability, validity) of the English-language IE-4, compared these psychometric properties with those of the German-language source version, and tested measurement invariance across both language … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 69 publications
0
3
1
1
Order By: Relevance
“…Further, as data was collected through an online survey, there is the possibility of a response bias, so future studies may choose to utilize alternative methods of data collection. Also, the reliability of the External Locus of Control scale in our study is significantly lower than in previous studies, such as in that conducted by Kovaleva et al (ranging from .53 to .63) [ 85 ] and in the study conducted by Nießen et al (ranging from .63 to .69) [ 86 ]. In future studies this should be taken into account and the sensitivity of this scale to intercultural differences should be reexamined.…”
Section: Discussioncontrasting
confidence: 90%
“…Further, as data was collected through an online survey, there is the possibility of a response bias, so future studies may choose to utilize alternative methods of data collection. Also, the reliability of the External Locus of Control scale in our study is significantly lower than in previous studies, such as in that conducted by Kovaleva et al (ranging from .53 to .63) [ 85 ] and in the study conducted by Nießen et al (ranging from .63 to .69) [ 86 ]. In future studies this should be taken into account and the sensitivity of this scale to intercultural differences should be reexamined.…”
Section: Discussioncontrasting
confidence: 90%
“…Our : α = 0.786, N = 4 In reliability tests, all metrics met the Cronbach's Alpha benchmark of 0.6 for internal consistency, except for the LOC variable. The LOC, informed by the I-E LOC scale from (Craig et al, 1984;Kovaleva, 2012;Nießen et al, 2022), showed a reduced Alpha because of its fouritem structure addressing both control dimensions. Despite this, LOC's reliability remained intact.…”
Section: Resultsmentioning
confidence: 99%
“…The Internal–External Locus of Control Short Scale–4 (IE-4; [ 43 ])/Internale–Externale-Kontrollüberzeugung–4 [ 44 ] measures internal and external locus of control with two items per factor. The 5-point Likert scale ranges from 1 ( does not apply at all ) to 5 ( applies completely ).…”
Section: Methodsmentioning
confidence: 99%